Teresa Ciepły - mistrzyni olimpijska z Bydgoszczy (1937-2006) (Kronika Bydgoska, 2010)
This is a documented story about the sports career of the famous athlete from the sports club WKS Zawisza. She came from a smali town in Łódzkie Voivodeship, where local teachers discovered her sprinter talent. She devel- oped this talent at the tum of the 1960’s, when she ran as a member of the Bydgoszcz sports club. She achieved her greatest successes at the Olympic Games in Tokyo in 1964, winning three medals - gold, silver and bronze.